2013
DOI: 10.1105/tpc.113.117820
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ACTIN-DEPOLYMERIZING FACTOR7 Severs Actin Filaments and Regulates Actin Cable Turnover to Promote Normal Pollen Tube Growth

Abstract: ORCID ID: 0000-0001-9517-2515 (S.H.).Actin filaments are often arranged into higher-order structures, such as the longitudinal actin cables that generate the reverse fountain cytoplasmic streaming pattern present in pollen tubes. While several actin binding proteins have been implicated in the generation of these cables, the mechanisms that regulate their dynamic turnover remain largely unknown. Here, we show that Arabidopsis thaliana ACTIN-DEPOLYMERIZING FACTOR7 (ADF7) is required for turnover of longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
157
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(165 citation statements)
references
References 94 publications
(167 reference statements)
6
157
0
Order By: Relevance
“…ADFs bind to and sever actin filaments, thereby acting as major regulators of F-actin dynamics (Henty et al, 2011;Zheng et al, 2013) implicated in regulating F-actin reorganization during stomatal closure and opening (Dong et al, 2001). Precise regulation of ADF activity is required for the correct balance between F-actin assembly and disassembly (Ressad et al, 1998;Bamburg, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ADFs bind to and sever actin filaments, thereby acting as major regulators of F-actin dynamics (Henty et al, 2011;Zheng et al, 2013) implicated in regulating F-actin reorganization during stomatal closure and opening (Dong et al, 2001). Precise regulation of ADF activity is required for the correct balance between F-actin assembly and disassembly (Ressad et al, 1998;Bamburg, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ADF5 and ADF9 in subclass III and ADF6 in subclass IV are expressed in a wide variety of tissues (Ruzicka et al, 2007). As in animal cells, ADFs in plants also bind to both monomeric and filamentous actins (Tian et al, 2009;Zheng et al, 2013) and regulate the organization of AFs (Zheng et al, 2013;Henty-Ridilla et al, 2014).…”
mentioning
confidence: 99%
“…Distinct organization patterns of the actin cytoskeleton are present in different regions of the pollen tube to maintain the polarized growth of cells. In the shank region, longitudinal actin cables exist throughout the cytoplasm, facilitating the transport of organelles and vesicles between the shank region and the subapex to support the reverse-fountain cytoplasmic streaming pattern (Ye et al, 2009;Cheung et al, 2010;Zheng et al, 2013;Duckney et al, 2017;Qu et al, 2017). At the subapex, actin filaments form regular structures in different species, such as the collar, fringe, mesh, or funnel, and some observations indicated that subapical F-actin could regulate the accumulation of vesicles and the growth of the tip region (Gibbon et al, 1999;Fu et al, 2001;Vidali et al, 2001;Chen et al, 2002;LovyWheeler et al, 2005;Qu et al, 2017).…”
mentioning
confidence: 99%
“…In Arabidopsis and lily (Lilium longiflorum), fimbrins (FIM), domain of Lin11, Isl-1, and Mec-3 proteins, actin-depolymerizing factors, several formins, and villins (VLN) have been shown to be involved in the formation and maintenance of longitudinal actin cables in the shank region of pollen tubes Zheng et al, 2013;Fu, 2015). VLN2, VLN5, AtFIM5, and LlFIM1 bundle apical PM-anchored F-actin and contribute to the formation of actin fringe or collar structures in the subapical region (Su et al, 2012;Qu et al, 2013;Zhang et al, 2016a).…”
mentioning
confidence: 99%